KARAKTERISASI POROSITAS NANOKARBON CANGKANG BUAH SAWIT MENGGUNAKAN SCANNING ELEKTRON MICROSCOPE (SEM) - Vivi Purwandari; Hestina Hestina; Zuhairiah Nasution; Hotromasari Dabukke; M Mukmin (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2021)
Referring to data from the Directorate General of Plantations of the Ministry of Agriculture throughout 2019, the area of oil palm plantations in Indonesia is estimated at around 14.68 million hectares, with total production reaching 51.8 million tons per year or the largest in the world. In 1 ton of palm oil produces 6.5% shell waste or 65 kg. Nanocarbons with their unique properties are now widely used in various applications such as batteries, supercapacitors, sensors and so on. Utilization of palm fruit shell waste as a nanocarbon material with a micropore structure, large surface area and high pore volume is the goal of this research.